The Effect Of Budget Participation On Managerial Performance With Psychological Capital And Job Relevant Information As Mediation Variables - Nila Munana; Elvin Bastian; Tri Lestari (FKIP, Universitas Banten Jaya, 2023)
The purpose of this study was to investigate the mediating impact of psychological capital and job relevant information on the budget participation to job performance at the public sector managers in the South Tangerang City Government. Data analyzed using SEM-PLS. The SEM-PLS allows the examination of the direct effects of budget participation on job performance and the indirect effects between budget participation and job performance that run through psychological capital and job relevant information. The findings of this study are that psychological capital fully mediates influence of budget participation to job performance, job relevant information fully mediates influence of budget participation to job performance. Limitations of this study are using questionnaire media to obtain primary data so that it relies on the level of respondent perception so that the subjectivity factor can be contained in it. Second limitation is generalizability of samples. Despite its limitations, this study has both academic and practical implications. The study adds to the job performance literature in a public sector organizations. The study also finds that manager’s job performance can be improved by minimizing Psycap and JRI. Future research should study other mediation variables on the effect of budget participation on job performance.